Operationalising Tawhidic Epistemology and the Ummatic Mind: a framework for disciplinary integration in Islamic higher education - Norman, Nurul Ain; Abdelaziz, Berghout (ISTAC-IIUM Publications, 2026)
In the post-colonial Muslim world, Islamic universities have been established with the noble aim of reviving the intellectual and civilisational legacy of Islam. Yet, despite decades of effort, the disconnection between Islamic metaphysical principles and modern disciplinary structures continues to plague Muslim higher education. While terms such as “Islamisation of Knowledge”, “Tawhidic Epistemology”, and “Integration of Knowledge” are frequently used, their practical application in the design of curricula, pedagogical methods, and research frameworks remains limited and often poorly understood. Osman Bakar aptly describes the state of many modern Islamic institutions as suffering from “an expanding body and a shrinking spirit,” where physical infrastructure and administrative growth outpace the development of an epistemological framework rooted in tawḥīd. 13 This has resulted in institutions that wear the “Islamic” label yet operate predominantly within secular epistemological models inherited from colonial paradigms. Such models often separate religious knowledge from worldly disciplines, creating a dualistic educational culture antithetical to the Islamic worldview. The root of this crisis is epistemological. As Bakar argues, the two testimonies of the Shahādah: "Lā ilāha illā Allāh, Muhammadur Rasūlullāh" must be understood as epistemological statements affirming the unity and Divine origin of all true knowledge.14 Tawḥīd is not merely a theological affirmation; it is the metaphysical and methodological foundation of all intellectual pursuit in Islam.15 Without its proper operationalisation, the university becomes just another modern institution, with Islamic terminology but no Islamic soul.